2020
DOI: 10.1021/acs.cgd.0c00883
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidation and High-Resolution Ultrasonic Temperature Sensor Based on Cr3+:MgAl2O4 Single Crystal Fiber

Abstract: High-quality pure MgAl 2 O 4 and Cr 3+ :MgAl 2 O 4 crystal fibers were grown using laser heating pedestal growth method successfully. The antioxidation ultrasonic temperature sensors (UTSs) were designed using MgAl 2 O 4 single crystal fibers (SCFs) as the acoustic waveguide for the first time. The ultrasonic velocity and the unit sensitivity were investigated, which illustrate that the MgAl 2 O 4 SCF-UTS is more sensitive compared with the YAG SCF-UTS because of the order−disorder phase transition of the spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[19] The maximum unit sensitivity of the Cr 3+ :MgAl 2 O 4 SCF-UTS was measured to be 43.94 ns C −1 m −1 , corresponding to a maximum resolution of 1.51 °C, representing record performance for SCF-UTS at that time. [20] Previous studies have found that a lower ultrasonic velocity and larger temperature-dependent velocity variation lead to higher sensor sensitivity. [20][21] The ultrasonic velocity of the crystal fibers is anisotropic and is mainly determined by the elastic properties and crystal density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] The maximum unit sensitivity of the Cr 3+ :MgAl 2 O 4 SCF-UTS was measured to be 43.94 ns C −1 m −1 , corresponding to a maximum resolution of 1.51 °C, representing record performance for SCF-UTS at that time. [20] Previous studies have found that a lower ultrasonic velocity and larger temperature-dependent velocity variation lead to higher sensor sensitivity. [20][21] The ultrasonic velocity of the crystal fibers is anisotropic and is mainly determined by the elastic properties and crystal density.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Previous studies have found that a lower ultrasonic velocity and larger temperature-dependent velocity variation lead to higher sensor sensitivity. [20][21] The ultrasonic velocity of the crystal fibers is anisotropic and is mainly determined by the elastic properties and crystal density. Therefore, orientation optimization and doping modification are feasible approaches for regulating the ultrasonic velocity, thereby improving the sensor performance.…”
Section: Introductionmentioning
confidence: 99%